2010
DOI: 10.1159/000317345
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Dietary α-Linolenic Acid Enhances Tissue Levels of Long-Chain n-3 PUFA when Linoleic Acid Intake Is Low in Hamsters

Abstract: Background/Aims: We tested whether feeding hamsters diets varying in α-linolenic acid (ALA) content and low in linoleic acid (LA) could increase the tissue levels of eicosapentaenoic acid (EPA), docosapentaenoic acid (DPA), and docosahexaenoic acid (DHA) to the same extent as a fish oil-supplemented diet. Methods: For 5 weeks, 60 hamsters were fed 1 of the following 5 diets containing 2% of total dietary energy (TE) as LA and either 0.5% (diet A), 1% (diets B and E), 2% (diet C), or 4% (diet D) ALA of TE, so t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…This is influenced by several factors including sex, genetic factors, physiological status and dietary factors ( 33 ) . High intake of LA and hence a high LA:ALA ratio could inhibit the conversion of ALA, which is supported by several animal studies ( 34 36 ) . However, recent human studies using a tracer isotope technique demonstrated that the conversion of ALA to LC n -3 PUFA is determined by the absolute levels of LA and ALA and not the ratio ( 37 ) .…”
Section: Discussionmentioning
confidence: 61%
“…This is influenced by several factors including sex, genetic factors, physiological status and dietary factors ( 33 ) . High intake of LA and hence a high LA:ALA ratio could inhibit the conversion of ALA, which is supported by several animal studies ( 34 36 ) . However, recent human studies using a tracer isotope technique demonstrated that the conversion of ALA to LC n -3 PUFA is determined by the absolute levels of LA and ALA and not the ratio ( 37 ) .…”
Section: Discussionmentioning
confidence: 61%
“…Studies have suggested that humans evolved on a diet containing approximately a 1:1 ratio of ω-6:ω-3 PUFA[7]; however, current western diets has a high ω-6:ω-3 ratio. [8] A diet high in ω-6 PUFAs, such as linoleic acid (LA), results in decreased tissue levels of ω-3 long-chain (Lc) PUFAs, including eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA)[9], and a heightened risk of chronic inflammatory disease processes. [10] In contrast, a diet containing a low ω-6:ω-3 PUFA ratio, or one that is supplemented with Lc ω-3 PUFAs, reduces risk factors for chronic inflammatory diseases, including cardiovascular disease,[11, 12] cancer,[13, 14] and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, DHA accumulation in ALA-fed animals is a tissue-selective process (Barceló -Goblijn & Murphy, 2009). In hamsters, diets containing 4% energy as ALA and 2% energy as linoleic acid (LA) can increase the tissue levels of EPA and DHA to the same extent as feeding 0.2% energy as fish oil (Aziz et al, 2010). As far as humans are concerned, regarding dietary PUFA n-3, only DHA accumulates in the membrane phospholipids (Jump, 2004), and the plasma DHA pool is far greater than that of EPA; therefore a small increment in the plasma DHA pool as a consequence of ALA conversion is usually hard to detect (Brenna, Salem, Sinclair, & Cunnane, 2009).…”
mentioning
confidence: 99%